Impact of Climate Change and Technology Adoption on Cereal Yields in South Asian Countries - Alvi, Shahzad; Jamil, Faisal (European Journal of Sustainable Development, 2018)
Over the past decade, scientists and economists have shown consensus that agricultural production is at high stake due to climatic changes. Crops are hit by droughts, floods, heavy or low levels of rainfall, humidity, decreasing water resources and increasing wind storms. On the other side, farmers are adopting new technology, which upholding the agricultural production. Considering these aspects, the present study examines the impact of climate change and technology adoption on cereal yields in South Asian countries. We develop an economic model that incorporates technology adoption, which is exogenously determined by farmers’ characteristics and market structure. Using the time series data from 1990 to 2015, we apply GMM econometric technique. The estimated results indicate that climate change decreases the cereal yields while the technology adoption increases the cereal yields. But the slow pace of technology adoption in the agriculture sector is a challenge to meet the food demand of the growing population in South Asian countries. This study suggests that these countries should increase the use of advanced technology and practices in agriculture sector to get sustainability in food production. Besides, there is the incessant need to reduce GHG emissions and population growth. Key words: Climate change; Technology adoption; Cereal yields; South Asia; Food sustainability